On Global Solutions of Systems of Nonlinear Functional Differential Equations with Deviating Argument Dependent on Unknown Functions - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
For a system of nonlinear functional differential equations with nonlinear deviations of an argument, we obtain sufficient conditions for the existence of a continuously differentiable solution bounded for t ∈ R.